Pertanggungjawaban Hukum Surety Company Terhada Obligee Atas Wanprestasi Oleh Principal Dalam Jaminan Performance Bond - Haslindra, Dinda Nopriansary (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
A breach of contract by the principal will result in losses that prevent the obligee’s rights from being fully satisfied. It is this breach of contract that will give rise to legal liability for the surety company, as the issuer of the performance bond, to compensate the obligee for losses resulting from the principal’s breach in accordance with applicable laws. Although the surety company is required to pay the claim directly, it is not uncommon for the obligee to receive only partial payment due to the fact that proving the breach of contract often leads to disputes. This study is a normative legal study supported by interview data, employing a statutory approach, a conceptual approach, and a case-based approach. Based on the research findings, the legal liability of a surety company regarding a performance bond under an agreement between the principal and the obligee is based on the principle of unconditional liability, meaning that claims must be paid immediately without the need for proof. If the obligee’s rights are not fulfilled, leading to a court dispute, legal action may be taken, accompanied by the presentation of evidence in court, until the claim is satisfied.